(untitled) (The Research of Medical Science Review, 2025)
Background: The different species of Plasmodium are the causative agents of malaria, and it is an obligate intracellular parasite spread by the bite of an infected female Anopheles mosquito. In underdeveloped nations, malaria causes high rates of morbidity and mortality, making it a major public health problem. Objective: This study was conducted to compare the efficacy of Rapid Diagnostic Test verses Microscopy for malarial diagnosis. Materials and Methods: This cross-sectional study was conducted at Bacha khan medical college Mardan from April 2024 to December 2024 to compare the efficacy of Rapid Diagnostic Testing Vs Microscopy for malarial diagnosis. A total of 150 blood samples from suspected malaria patients were included in our study. Their blood samples were aseptically drawn and dispensed into an EDTA container for RDTs and microscopic analysis. All the data was analyzed by using SPSS version 24. Results: This study included 150 patients based on the inclusion criteria. Of them, 80 (53.3%) were male and 70 (46.6%) were female. 100 patients (66.6%) had positive microscopy results for malaria, 40 individuals (26.6%) had positive RDT results, and 50 individuals (3.3%) who had negative microscopy results also had negative RDT results. Conclusion: This study demonstrates that malaria can be diagnosed more accurately using microscopy. Importantly, a negative malaria test result by RDT may not always indicate absence of malaria. According to our study, microscopy is the gold standard in diagnosing malaria when compared to RDT.